Diseño de una guía metodológica para la integración de las normas ISO 9001:2008 y OHSAS 18001:2007 en el proceso productivo para la empresa Muebles & Accesorios. (2015)
The production process of the company Muebles & Accesorios does not have a management system based on the standards NTC-ISO 9001: 2008 and NTC-OHSAS 18001: 2007, which has led to reprocessing, production, unnecessary inventories, complaints and claims in the clients, and lack of physical, mental and social well-being in the workers. A diagnosis was made of the current situation of the organization with the participation of different levels: manager, supervisor, coordinator and operator; A survey was carried out in which the debits of the standard NTC-ISO 9001: 2008 and NTC-OHSAS 18001: 2007 were identified. It was identified that the organization does not meet most of the requirements of the standards, it could be determined that the company has isolated, undocumented information of the production process, which does not allow tracking, planning and traceability of the quality criteria, and of safety and health at work. So the general objective of the work is to design a methodological guide for the integration of the standards NTC-ISO 9001: 2008 and NTC-OHSAS 18001: 2007 in the production process for the company Furniture & Accessories, looking for a continuous improvement in the integrated management in quality and safety and health in the workplace. Through the information collected a report was made that includes the current situation of the company, and improvement options in order to meet the requirements set out in the standards. Subsequently, the implementation guide was designed, so that the company follows the guidelines stipulated therein, and thus be able to have controlled processes and procedures that meet the requirements established by the interested parties.